Prevalence of depression and its related factors among older adults in Indonesian nursing homes - Indra Gunawan; Xuan-Yi Huang (Belitung Nursing Journal, 2022)
Background: Depression is one of the most severe mental disorders experienced by older adults worldwide. The prevalence of depression among older adults in nursing homes is three-time higher than in the community. Therefore, knowing the incident rates of depression and its related factors would help provide appropriate intervention and prevention programs in the future. Objectives: The study aimed to determine the prevalence of depression and compare the difference in depression status according to the sociodemographic characteristic of the older adults in the Indonesian nursing homes.    Methods: A descriptive cross-sectional study design was used in this study, which involved 116 participants selected using convenience sampling from five different general nursing homes in Bandung City, Indonesia. The Short Form (SF) of the Geriatric Depression Scale (GDS) was used to evaluate depression among older adults in nursing homes. The t-test and one-way ANOVA were used for data analysis. Results: Of the total participants, 56.9% had depression, which 7.8% with mild depression, 37.1% with moderate depression, and 12% with severe depression. In addition, there were significant differences in depression according to age, gender, marital status, educational background, ethnicity, disease history, duration of stay, and the visitor frequency among the older adults in nursing homes (p <.001). Conclusion: A high rate of depression among older adults in Indonesian nursing homes was identified. Therefore, attention to caring for more specific needs, such as the psychosocial needs of older adults in nursing homes, is urgent.